2018
DOI: 10.3389/fendo.2018.00304
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin-3 Genes and Peptides Characterized in a Basal Teleost, the European Eel: Evolutionary Perspective and Pituitary Role

Abstract: In mammals, neurokinin B (NKB) is a short peptide encoded by the gene tac3. It is involved in the brain control of reproduction by stimulating gonadotropin-releasing hormone (GnRH) neurons, mainly via kisspeptin. We investigated tac3 genes and peptides in a basal teleost, the European eel, which shows an atypical blockade of the sexual maturation at a prepubertal stage. Two tac3 paralogous genes (tac3a and tac3b) were identified in the eel genome, each encoding two peptides (NKBa or b and NKB-related peptide N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 79 publications
(184 reference statements)
2
18
0
Order By: Relevance
“…One of the peptides that was generated by the processing of the Tac3 precursors was similar to the mammalian NKB, while the second related peptide was termed NKF due to its existence only in fish and frogs (20). Treatment with NKB peptides caused an increase in both FSH and LH synthesis and release in zebrafish (20), tilapia (23), goldfish (21), striped bass ( Morone saxatilis ) (42) and orange spotted grouper ( Epinephelus coioides ) (43) while in the European eel, human NKB was found to inhibit the expression of lhβ (22). Moreover, NKB and NKF bound and activated Tac3 receptors of zebrafish (20) and tilapia (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the peptides that was generated by the processing of the Tac3 precursors was similar to the mammalian NKB, while the second related peptide was termed NKF due to its existence only in fish and frogs (20). Treatment with NKB peptides caused an increase in both FSH and LH synthesis and release in zebrafish (20), tilapia (23), goldfish (21), striped bass ( Morone saxatilis ) (42) and orange spotted grouper ( Epinephelus coioides ) (43) while in the European eel, human NKB was found to inhibit the expression of lhβ (22). Moreover, NKB and NKF bound and activated Tac3 receptors of zebrafish (20) and tilapia (23).…”
Section: Discussionmentioning
confidence: 99%
“…Like kisspeptin, humans carrying loss-of-function mutations in neurokinin B [NKB; also known as tachykinin 3 (Tac3)] or in NKBR also display hypogonadotropic hypogonadism (19). The first indication that NKB is widely expressed in fish species and has a stimulatory reproductive effect was shown in zebrafish (20), goldfish ( Carassius auratus ) (21), European eel ( Anguilla Anguilla ) (22) and tilapia (23). Teleost have one or two tac3 genes that encodes two mature peptides, NKB and NKB-related peptide (also called neurokinin F (NKF), and two tac3r genes (Tac3ra and Tac3rb) (20, 23).…”
Section: Introductionmentioning
confidence: 99%
“…Tac1 and Tac3 have also been identified from zebrafish, and the Tac3 prototype gene appears to have duplicated to give rise to Tac3a and Tac3b (Biran et al, 2012) as shown in Figure 4. In addition, two Tac3 have also been characterized from an eel, Anguilla anguilla , that is a basal vertebrate (Campo et al, 2018). Due to teleost-specific whole genome duplication multiple Tac3 genes were generated in teleost fish (Moriyama and Koshiba-Takeuchi, 2018).…”
Section: Structure Of Tachykinin Peptides and Organization Of Genes Ementioning
confidence: 99%
“…Gnrh-r1a and gnrh-r1b expressions were below the threshold of detection in primary cultures of pituitary cells (Campo et al, 2018;Pasquier et al, 2018), and were thus not assayed in this study.…”
Section: Other Gene Primersmentioning
confidence: 99%